Board of directors’ attributes and occurrence of corporate fraud among Malaysian listed corporations - Mohd Nasir, Ahsani (2021)
Board of directors is an integral part of internal mechanism of corporate governance. A well-functioning an effective board of directors with the right attributes is instrumental in acting as monitor against any corporate transgression. This is especially so for Malaysian listed corporations where there is reported prevalence of corporate fraud despite many regulatory efforts to promote better practice of corporate governance. This paper seeks to investigate the attributes of board of directors from the perspective of representation of women directors, directors with legal qualification, executive chairman as well as the board size and its influence towards the occurrence of corporate fraud. A sample of 53 listed companies in Bursa Malaysia that were the subject of Securities Commission Malaysia enforcement action either by way of criminal prosecution, civil action, administrative action or compound were used as a proxy for occurrence of corporate fraud. These companies were matched with another 53 companies that are listed in Bursa Malaysia that were not the subject of enforcement actions. This study covers the period of enforcement actions from 1999 to 2019. Binary logistics regression analysis is utilized to analyse the data gathered. The findings of this study shows that there is evidence of positive influence of the board size on the occurrence of corporate fraud, where a larger board size would likely to reduce the probability of corporate fraud occurrence. However, there is insufficient evidence to establish the occurrence of corporate fraud with the presence of women directors, legally qualified directors and executive chairman.